PHYTOTOXIC, ANTIOXIDANT, ANTIBACTERIAL, AND ANTILEISHMANIAL ACTIVITIES OF EUPHORBIA HIRTA FROM CHITWAN DISTRICT NEPAL - RAJ SHARMA, KHAGA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The aim of this study is to investigate the antimicrobial, antioxidant, antileishmanial, and phytotoxic activities and estimation of total phenolic and flavonoid contents in methanol extract of Euphorbia hirta collected from Chitwan district of Nepal using in vitro studies. Methods: Methanol extract of the plant was prepared by cold percolation method. Screening of secondary metabolites was performed by color differentiation methods. The in vitro antioxidant potential of the plant extract was evaluated by 2,2-diphenyl-1-picrylhydrazyl assay in which percentage scavenging and inhibitory concentration (IC50) were calculated. Furthermore, antileishmanial and phytotoxic activity was evaluated by adopting the standard protocols. Phenolic and flavonoid content was estimated using Folin–Ciocalteu phenol reagent and aluminum chloride colorimetric method, respectively. The antimicrobial activity was evaluated by agar well diffusion method. Results: The antileishmanial activity of the methanolic extract of E. hirta showed low leishmanicidal activity IC50 68.1±1.2 μg/ml standard deviation (SD) as compared to the standard drugs amphotericin B 0.29±0.05 μg/ml SD and pentamidine 5.09±0.09 μg/ml SD. The radical scavenging activity shows IC50=29.23±0.21 μg/ml SD which is found potent than the standard ascorbic acid IC50=45.93 μg/ml. The extract of E. hirta contains high value of total phenolic content milligram gallic acid equivalent per gram (138.10±4.90 mg GAE/g SD) and flavonoid content milligram quercetin equivalent per gram (11.54±0.00 mg QE/g SD). The plant extract exhibits weak antibacterial activity against Staphylococcus aureus (9.0 mm), Bacillus subtilis (11.0 mm), Escherichia coli (9.0 mm), and Salmonella Typhi (9.0 mm) at a concentration of 10.0 mg/ml in which 50 μl was loaded per well. Plant extract exhibits moderate phytotoxic activity with the number of fronds 3, 10, and 14 against the different concentrations of plant extract. Conclusions: The preliminary results of this study have put forward E. hirta into promising herbs with good antioxidant activities, moderate phytotoxic activity, and potential source of antibacterial agent with a significant amount of total phenolic and flavonoid contents. Although the plant extract shows the potent biological activity, further studies are needed to assess its mechanism of action.